From Central Iran to Petra: Hieronymus of Cardia, Eye-witness in Diodorus Siculus’ Book 19 - Polański, Tomasz (Anabasis. Studia Classica et Orientalia, 2020)
Hieronymus of Cardia was an eye-witness of the crucial events of his times. He visited places and countries from the Mainland Greece and the Aegean to the interior of Asia. I would like to limit myself to a single premise: the argument of style and personal observation. I think that Diodorus’ Book 19 was largely composed by one author – Hieronymus of Cardia. It is conspicuous for its high-quality epic style, characterized by a wide range of tone and subtle differences. The style is highly individualised and remarkable for its penchant for orientalism and exoticism. Here I am thinking of the passages which refer to the Levant, Mesopotamia and Iran (Susiana, Central Iran, Petra, the Dead Sea).